Validasi Metode Penentuan Kandungan Kafein dalam Teh Hijau dengan FTIR - Isnaini, Nur (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
The FTIR UATR method for quantifying caffeine in green tea samples was validated. ATR (Attenuated Total Reflectance) , a technique for direct analysis without sample preparation, was employed. Caffeine was determined at peak absorption between 1600 and 1700 cm-1. Calibration using standard concentrations from 0 to 5% yielded excellent linearity with a correlation coefficient value of 0.9978. Precision, measured as % RSD (2.8369%), met the acceptable limit of 2/3 the Horwitz CV (4.5323). Accuracy was confirmed through spiking, resulting in a recovery of 100.3%, within the acceptable range of 95-105%. These findings demonstrate the suitability of this method for caffeine analysis in green tea samples.